Evaluation of Students' Skills in Software Project - Cihan, Pinar; Kalipsiz, Oya (ASSOC INFORMATION COMMUNICATION TECHNOLOGY EDUCATION & SCIENCE, 2014)
Software project probably is a sector that has witnessed the highest rate of project failure in the world. The industry claims that the software engineering graduates are not able to meet their requirements in software industry. This is surprising to the academia that offers software engineering specialization. This type of situation is creating the barrier between the software industry and academics and the efforts are made to reduce the gap. So it is important identify weaknesses of projects. This paper outlines evaluating questionnaire about the student projects in software development courses student projects. The questions were intended to test students' soft skills and hard skills. This questionnaires performed Software Engineering, System Analysis and Design, and Agile Software Development courses in the Department of Computer Engineering. All of these courses are project based learning. In this study, soft skills and hard skills in software development courses students project evaluated. The purpose of this study identify the students project weaknesses in project based courses to provide better quality education in software development courses, preparing students for professional life, improvement of the success rate of software projects and possibly lead to reduce gap between academy and industry.
Keywords: Software engineering education; Software engineering industry; Quality assurance in education; Soft skills; hard skills; Computer Science